Our daily bread [videorecording (DVD)] - Geyrhalter, Nikolaus, 1972- (Icarus Films Home Video, 2006)
A spectacular visual essay composed of epic tableaus, a haunting vision of our modern food industry, and the methods and technology utilized for mass production.